Mechanical properties of cement sand brick containing sawdust as partial fine aggregate replacement - Nurul Hanierah, Hamdani (2017)
Cement sand brick is a type of brick made from a mixture of cement and sand. The characteristics of sand are the main reason why it is in great demand in the construction industry. On the other hand, sawdust is a solid waste from industrial sector mainly generated from sawmills that is usually dumped at landfill. Surprisingly, the characteristics of both materials which are sand and sawdust are almost identical. By replacing sand with sawdust, sand mining and waste disposal problems can be reduced as well as economical cement sand brick can be produced. This study aims to investigate the effect of sawdust as partial sand replacement on the properties of cement sand brick. In this study, five different percentages of sawdust for each test strength to be used as fine aggregate replacement which are 2%, 4%, 6%, 8% and 10% to produce a several types of cement sand brick. The field of studies also covers important parameters including compressive strength, flexural strength, and water absorption in determining the engineering properties. The brick size used 215 x 102.5 x 65 mm were casted and their strength evaluated at 7, 14 and 28 days. The findings show that the samples with 2% of sawdust are comparable strength value with control cement sand brick of compressive and flexural strengths. It also has the lowest moisture absorption compared to other samples.